Marine and Coastal Environments: Challenges, Impacts, and Strategies for a Sustainable Future - Ahmed, Rashed; Tamim, Md. Tanzimur Rahman (Balai Publikasi Indonesia, 2025)
Marine and coastal environments are critical interfaces of biodiversity and ecological significance, encompassing estuaries, mangroves, coral reefs, seagrass meadows, and beaches. This article examines the historical evolution, current challenges, and future prospects of these vital ecosystems, utilizing extensive literature review and online research to analyze the impacts of climate change and human intervention.. This study reviews the historical evolution of these ecosystems, highlighting their significance as centers of human sustenance, trade, and culture. It evaluates the severe impacts of global warming—rising sea levels, ocean acidification, and habitat destruction—and human activities such as overfishing, pollution, and coastal development, which exacerbate ecosystem degradation. Methodologies include an extensive literature review and online research to assess ecosystem services, threats, and conservation strategies. The research underscores the socio-economic implications of deteriorating marine habitats, such as threats to fisheries and heightened vulnerability to extreme weather events. The findings advocate for proactive conservation through marine protected areas, habitat restoration, and sustainable practices. International cooperation, guided by initiatives like the United Nations Decade on Ecosystem Restoration, is emphasized as critical for enhancing resilience. Looking ahead, the article discusses adaptation and mitigation strategies essential for safeguarding marine environments against the escalating impacts of global warming, ensuring their sustainability for future generations.